Utilizing Jackfruit Leaf Ash as a Glaze in Ceramic Art - Suprabanindya, Caecilia Tridjata; Petrus, Himawan Tri Bayu Murti; Hazmi, Fariz Al (Institut Seni Indonesia Padang Panjang, 2025)
The objective of this research was to apply ash glaze—specifically jackfruit leaf ash—to ceramic works in order to enhance their aesthetic value. The study involved expertise from both fine arts, particularly ceramic art, and chemical engineering, and was conducted using an inquiry-based research approach. An experimental method was employed, specifically a pre-experimental intact-group comparison design, with samples divided into four formulas containing different ash mixtures. In this study, organic ash was blended with Kebumen soil, Sukabumi soil, and ready-to-use transparent glazes (F.107 and F.3T). The results demonstrated that jackfruit leaf ash glaze produced unique textural characteristics and natural color tones (including white-gray, cream, beige, and brown), with transparent, opaque, and semi-matte glaze qualities. Furthermore, this ash glaze was applied as a decorative finish on functional ceramic craft products, either as a single formula, in combination with other jackfruit ash glaze formulas, or with the addition of oxide colorants. Adjustments were also made to the glaze composition percentages to achieve varied visual effects. The ceramics used in this study were made from Sukabumi clay, which proved to be well-suited to the jackfruit leaf ash glaze formulation.